Assessment of Vitamin D Deficiency Prevalence among Type 2 Diabetes Mellitus Patients in a South Indian Tertiary Care Hospital - Senthilkumar Kalimuthu; Sachu Philip; Natarajan Elango Nandhini; Lalamiya Abdul Rahiman Baba; Shanmugasundaram Ravichandran (Journal of Experimental Life Science)
Vitamin D deficiency has become a global health issue and is associated with the multifactorial clinical manifestations of diabetes. The objective of this study is to analyze vitamin D deficiency in T2DM patients in association with biochemical parameters and thyroid-stimulating hormone (TSH). This study was a cross-sectional study in a tertiary care hospital conducted after the Institutional Ethical Committee (IEC) approval. The available descriptive data of patients, such as age, gender, biochemical parameters, TSH, and glycated hemoglobin (HbA1c), were collected. Vitamin D was measured using the enzyme-linked immunosorbent assay (ELISA) method. The descriptive parameters were statistically analyzed using chi-square analysis. The results comprise 322 T2DM patients, with 187 males and 135 females. Vitamin D status levels were observed to have severe deficiency < 10 ng.mL-1 (23.6%), deficiency >10-20 ng.mL-1 (42.2%), insufficient >20-29 ng.mL-1 (22.7%), and sufficient > 30 ng.mL-1 (11.5%). The male and female patients with vitamin D status were significantly (p<0.001) different between groups. No significant (p = 0.122) association was observed between HbA1c and vitamin D. The high status of vitamin D deficiency with high glycemic levels is associated with poor diabetic control. Therefore, patients require awareness about their vitamin D status; with a proper diet, adequate exposure to sunlight, and exercise can help them improve their health.